IMPACT OF MGNREGA IN TERMS OF DIRECT CHANGES- A STUDY IN SRIKAKULAM DISTRICT OF ANDHRA PRADESH - K. ARCHANA (The Journal of Research ANGRAU, 2023)
The study examined the impact of MGNREGA in terms of direct changes experienced by the beneficiaries during the year 2015. One hundred and twenty(120) respondents were selected randomly for the study. The results revealed that majority of the MGNREGA beneficiaries’ experienced medium direct changes followed by high and low direct changes. Direct changes observed due to implementation of MGNREGA were increased employment generation (286 days/ year), increased number of employed persons in the family (3 or more), increased daily working hours (> 7 hours), increased daily wage rates (360/- Rs.), increased income generation, increased community and individual assets creation and reduced migration (47 days/ year)